NEIGHBORHOOD EFFECTS IN THE SOLOW MODEL WITH SPATIAL EXTERNALITIES - Wilfried Koch (European Regional Science Association (ERSA), 2005)
Recent theoretical and empirical work generally often focus on the interdependence of nations and regions underlying that the economy of one country or region is not independent of the economies of others. However, these models generally ignores the impact of location and neighborhood in explaining growth. This paper presents an augmented Solow model that includes spatial externalities and spatial interdependence among economies. We obtain a spatial econometric reduce form which allows testing the effects of the rate of saving and the rate of population growth on income per capita. Finally, we use the propriety of spatial multiplier effect in order to evaluate the impact of a shock on saving rate on european regional disparities.
Keywords: 330